Aberrant investor participation amid substantial price swings: high-frequency evidence of magnet-repellent effect from Malaysia - Sifat, Imtiaz Mohammad; Mohamad, Azhar; Hamid, Zarinah (Routledge, 2019)
Price limits have skirted controversy since inception. Regulators claim limits curb volatility, allay stressed markets, and encourage reflection on information to trade rationally. Opponents contend saying limits delay the inevitable by postponing volatility, deferring equilibrium price discovery, and obtrude investors’ trading plans. While these undesired effects are all ex-post in nature, some argue that limits – by very existence – threaten to invite trading activities towards themselves and govern trade-flow such that the limit’s prophecy is fulfilled. This is known as magnet effect. Theoretical development of this ex-ante effect has been in hibernation since the 1990s. Thus, empirical attempts have been made to test its existence – mostly in East-Asian exchanges with tight limits. Bursa Malaysia, however, defends its ±30% limit for ~30 years based on internal (unpublished) studies. This paper employs a battery of tests to examine the existence and magnitude of magnet effect and – its counterpart – repellent effect in Malaysia. Our findings suggest a weak form of magnet effect and comparable degrees of repellent effect. Moreover, we report price acceleration beyond a threshold point unsupported by order aggression or volume support necessary to constitute a magnet effect. We discuss policy import of our findings and recommend future research avenues worthy of pursuit. Price limits’ opponents argue that limits can threaten to invite trading activities towards themselves such that the limit’s prophecy is fulfilled. Existence of this phenomenon—the magnet effect—has been tested mostly in exchanges with tight limits. This paper employs a battery of tests to examine the existence and magnitude of magnet effect in Bursa Malaysia, which employs a wide price limit. Our findings suggest a weak form of magnet effect and comparable degrees of repellent effect. Moreover, we report price acceleration beyond a threshold point unsupported by order aggression or volume support necessary to constitute magnet effect.